The corporate playbook: A self-serving myth - Christopher Snowdon (Institute of Economic Affairs (IEA), 2025)
This paper argues that the academic literature on the political strategies of 'unhealthy commodity industries' offers no insights into political science because the tactics identified are not specific to those industries. Without a control group of benign or healthy industries to compare them to, public health academics have failed to demonstrate that there is anything distinctive or unique about the 'corporate playbook'. Since most or all of the same tactics have been identified whenever the scope has been expanded to include industries as diverse as baby formula, social media and pharmaceuticals, it seems likely that any industry would employ similar strategies if they faced similar political pressure from activists. A further failing of the 'corporate playbook' framing is that it does not compare the political strategies of industry and nonindustry opponents to paternalistic regulation. In the absence of such an analysis, it is unclear from this literature whether the political activity of industry groups differs from that of broader civil society. It seems, however, that it does not. It is notable that public health groups employ nearly all of the strategies in the 'tobacco playbook' when campaigning for legislation. With some narrow exceptions, the tactics that are said to make up the 'corporate playbook' of 'unhealthy commodity industries' are standard elements of political activity in democratic societies and are used by industry and non-industry actors alike. The claim that 'unhealthy commodity industries' use the same strategies or follow the 'tobacco playbook' is fatuous and only has value as a rhetorical device for public health actors to use as part of their own political activity, most often when seeking to exclude opponents from the policy-making process.
Keywords: 330